The Sustainability of Contract Farming Model: A Case Study of an Agribusiness Company - Eka Nurjati; Fransisca Susanti Wiryawan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
The benefits of the agricultural partnership for companies are achieving supply continuity and quality. Meanwhile, partner farmers get price guarantees and marketing certainty. However, several aspects threaten sustainability. As a case study of PT SSS, this research used qualitative descriptive analysis. The results of the situational analysis show that the performance of PT SSS in 2021 is positive as reflected in the sales, profits, market share, and additional workforce, while the performance of partner farmers also is positive during the partnership with the company. There are two partnership patterns adopted by PT SSS, i.e. the plasma core and the trading partnership. In the plasma core partnership, the partner company is obliged to accommodate the partner farmers’ harvests according to the agreed quantity and price and the company provides agricultural input credit. Trade partnerships are carried out if the supply of plasma core partnerships is not met. Problem analysis based on the fishbone method includes four dimensions, i.e. economic, social, environmental, and governmental. The policy implications needed are: 1) Strengthening the commitment to continue mutually beneficial partnerships, 2) Written partnership contracts containing rights and obligations, rewards, and punishments, 3) Establishment of farmer insurance, activation of farmer groups, and mentoring and counseling programs, 4) Adoption of more environmentally friendly technology and improvement of farm’s and company’s efficiency, 5) The adoption of innovation in marketing, products, and methods/processes/production techniques for PT SSS, 6) Government’s commitment to reconsider land conversion, 7) Coordination with the government regarding the accessibility and affordability of subsidized fertilizers. Both the partner farmers and the company are committed to continuing contract farming, but there are technical aspects that need to be followed up and require the commitment of various stakeholders.